2015
DOI: 10.1038/srep16279
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal super-resolution optical microscopy visualizes the close connection between membrane and the cytoskeleton in liver sinusoidal endothelial cell fenestrations

Abstract: Liver sinusoidal endothelial cells (LSECs) act as a filter between blood and the hepatocytes. LSECs are highly fenestrated cells; they contain transcellular pores with diameters between 50 to 200 nm. The small sizes of the fenestrae have so far prohibited any functional analysis with standard and advanced light microscopy techniques. Only the advent of super-resolution optical fluorescence microscopy now permits the recording of such small cellular structures. Here, we demonstrate the complementary use of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…However, because of the impossibility in performing proper fenestration measurements in the live cells, in the current work, we were forced to use glutaraldehyde‐fixed LSECs. The LSEC fenestrations are surrounded by the cytoskeleton ring made of actin in the form of a calmodulin‐actomyosin complex that is responsible for their diameter . Therefore, according to Targosz‐Korecka et al, information about their structure should be preserved after fixation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the impossibility in performing proper fenestration measurements in the live cells, in the current work, we were forced to use glutaraldehyde‐fixed LSECs. The LSEC fenestrations are surrounded by the cytoskeleton ring made of actin in the form of a calmodulin‐actomyosin complex that is responsible for their diameter . Therefore, according to Targosz‐Korecka et al, information about their structure should be preserved after fixation.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the publications, the structure of fenestrations in LSECs was described in fixed cells using electron microscopy, atomic force microscopy (AFM) or recently super‐resolution optical microscopy . However, in fixed (especially fixed‐dried) cells, the structure of fenestrations might be altered .…”
Section: Introductionmentioning
confidence: 99%
“…Liver sinusoidal endothelial cells exhibit a pore-like structure which allows the filtration of objects between the blot and hepatocytes based on size selection. The spatial distribution of the cytoskeleton and plasma membrane was observed in liver sinusoidal endothelial cells using combination 3D-SIM and STORM microscopy, revealing a close association between the membrane and cytoskeleton 147 . A periodic structure of actin, spectrin, ankyrin and sodium channels was shown in neuronal axons using STORM microscopy, revealing a strikingly regular assembly of these cytoskeletal elements 148 .…”
Section: Super-resolution Investigations Of Biological Membranesmentioning
confidence: 99%
“…The resolution limit of these technics allows to detect fenestrae regardless their small size and their high representation in LSECs membranes. Using three-dimensional structured illumination microscopy (3D-SIM) and direct stochastic optical reconstruction microscopy (dSTORM), Monkemoller et al (2014Monkemoller et al ( , 2015 [Cogger et al, 2010;Zapotoczny et al, 2017] recently observed fenestrae in optical ways and tried to analyse their dynamics and co-localised actin filaments that surround fenestrae.…”
Section: Introductionmentioning
confidence: 99%